The Effectiveness of Sensory Circle Time (SenCleTi) Media to Improve Sensory Motor Skills in Early Childhood - Winda Sherly Utami; Sri Indriani Harianja; Masyunita Siregar; Nyimas Muazzomi; Tohap Pandapotan Simaremare (FKIP Universitas Lampung, 2024)
The Effectiveness of Sensory Circle Time (SenCleTi) to Improve Sensory Motor Skills in Early Childhood. Objectives: This study aims to determine the effectiveness of sensory circle time media (SenCleTi) in improving sensory motor skills of children aged 4-5 years, Methods: This study is a quantitative study that uses an equivalent time series design type exp eriment research design by measuring the posttest value of children in the experimental group. The test subjects in this study were group A children aged 4-5 years at Melati 2 Kindergarten, Jambi City, totaling 15 people. Data collection was obtained from observations carried out in a structured manner by determining the instruments to be observed. Observations are assessed using observation guidelines in the form of a checklist arranged on a Likert scale. Data were analyzed using inferential statistical analysis techniques N-Gain score test, Findings: The results obtained are sensory circle time media (SenCleTi) is declared effective to improve the sensory motor skills of children aged 4-5 years as evidenced by the results of the N-Gain score test which obtained a value of 0.78 with a percentage of 78% which is included in the high and effective category, and Conclusion: Sensory motor skills of 4-5 years old children are proven to increase by using sensory circle time (SenCleTi) media during learning activities. Therefore, this innovative education-based media can be one of the media that teachers can use in training the sensory motor skills of children aged 4-5 years. Keywords: sensory circle time media, sensory motor, early childhood.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202488